THE EXISTENCE OF GENE DNA POLYMERASE MUTATION FROM POSITIVE HEPATITIS B SAMPLES IN BANDUNG, INDONESIA - Rostinawati, Tina Rostinawati; Retnoningrum, Debbie Sofie; Pratiwi, Desi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To complete mutation existence in reverse transcriptase domain of the viral Polymerase. Methods: The study was done by amplification step of viral polymerase gene fragment, agarose gel electrophoresis, PCR product purification with GFX column kit, sequencing and sequencing result analysis. The samples were derived from Clinical Laboratory in Bandung Indonesia. Results: The result showed mutations in DNA fragment encoding for RT domain viral polymerase in sample 6, 7 and 8. There were mutations leading to amino acid substitution L526S in sample 6, D551E in sample 7 and D552E in sample 8. Conclusion: D551E and D552E substitution occurred in YMDD motif RT DNA polymerase that produced YMDE mutant. L526S, D551E and D552E were estimated as antivirus-resistance mutants that have never been reported before.